2017
DOI: 10.1515/pjvs-2017-0038
|View full text |Cite
|
Sign up to set email alerts
|

Effect of feeding with bilberry fruit on the expression pattern of αCaMKII in hippocampal neurons in normal and diabetic rats

Abstract: AbstractαCaMKII, widely occurring in the central nervous system, plays a significant role in cognitive processes. It is well known that diabetes is a risk factor that may trigger brain atrophy, cognitive dysfunction and finally lead to memory loss. Antioxidants richly present in bilberry fruits are believed to have significant effects on diabetes-related brain dysfunctions mainly due to their abilities to modulate neurotransmitter release that lead to reduction of the negative impact of free radicals on cognit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…At present, there is little information in the literature on the impact of bilberries on the CNS in the course of diabetes. The previous, pioneer study by the authors of the current study showed that antioxidants present in bilberry fruit affect morphology, and probably show beneficial effects on hippocampal neurons during diabetes [39]. It was also shown that long-term supplementation with bilberry extract prevents learning deficits, as discussed by Subash et al [47].…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…At present, there is little information in the literature on the impact of bilberries on the CNS in the course of diabetes. The previous, pioneer study by the authors of the current study showed that antioxidants present in bilberry fruit affect morphology, and probably show beneficial effects on hippocampal neurons during diabetes [39]. It was also shown that long-term supplementation with bilberry extract prevents learning deficits, as discussed by Subash et al [47].…”
Section: Discussionsupporting
confidence: 63%
“…Although the peripheral effects of bilberry in living organisms are ambiguous, its role in the treatment of DM is still important and needs to be explored. In addition, DM also resulted in the disruption of glucose homeostasis in the CNS [39]. Several reports have shown that cognitive functions are disturbed in the course of diabetes, which is associated with structural and electrophysiological alterations and brain atrophy [14,40].…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, they are used in diabetes-related research to try to prevent and repair some of the brain damage caused by diabetes, particularly tissue loss and reduction in cognitive function and memory [ 90 ]. It was found that bilberries were able to modulate neurodegeneration in diabetic rats by increasing neurotransmitter release and reducing the quantity of ROS in the brain [ 90 ]. The researchers also note that the extract was able to promote healthy morphological modulations in αCaMKII in hippocampal neurons.…”
Section: Neurodegenerative Mechanisms Associated With Ros and Effementioning
confidence: 99%
“…Matysek et al (2017) during an investigation on diabetic rats demonstrated that treatment with V. myrtillus fruits causes increase in αCaMKII‐positive nerve fibers length in the hippocampus tissue compared to control group. Calcium/calmodulin‐dependent protein kinase II (CaMKII) is a kinase that found in hippocampus and it is a key factor in learning, memory and behavior.…”
Section: Resultsmentioning
confidence: 99%